Sustainability Reporting Academic Research: A Bibliometric Trends and Future Directions - Mohamed, Ali Ibrahim; Awale, Abdirahman Abdinur; Mohamed, Mohamed Ismail (International Journal of Economics and Financial Issues, 2025)
Sustainability reporting has emerged as a critical area for businesses, governments, and society, reflecting a growing emphasis on transparent environmental, social, and governance (ESG) practices. Despite its importance, there is a limited understanding of bibliometric trends within this field. This study aims to examine recent sustainability reporting studies and explore how bibliometric analysis can shape future research directions. Utilizing a bibliometric approach, we analyzed 2,282 scholarly publications on sustainability reporting from 2010 to 2024, sourced from the Scopus database. VOSviewer software was employed to map and visualize patterns in authorship, countries, journals, keywords, and collaboration networks. The findings reveal a significant upward trend in sustainability reporting publications, especially after 2019, indicating heightened global focus on sustainability issues. The United Kingdom and the United States lead in research contributions, with substantial participation from Italy, Australia, and Germany. Key journals identified include the journal of cleaner production and corporate social responsibility and environmental management. Keyword analysis highlights central themes such as “sustainability reporting,” “global reporting initiative,” and “sustainable development.” Influential authors and collaborative networks were mapped, showcasing the interconnectedness within the research community. The study concludes that while sustainability reporting research has grown notably, many areas remain underexplored. Expanding research to less-focused topics, refining theoretical frameworks, and incorporating diverse stakeholder perspectives are crucial for advancing the field. This comprehensive review provides valuable insights into the current state of sustainability reporting research and identifies potential areas for future exploration, contributing to the promotion of transparency, accountability, and ethical corporate practices.